Comparing three different phenotypic methods for accurate detection of carbapenemase-producing Enterobacterales. Issue 6 (June 2021) - Liao, Quanfeng; Yuan, Yu; Li, Qingrong; Wu, Siying; Liu, Ya; Zhang, Weili; Xiao, Yuling; Kang, Mei
Abstract: Background: Early identification of carbapenemase-producing Enterobacterales (CPE) is highly essential to prevent their dissemination within health care settings. Objective: This study aimed to compare 3 reported phenotypic assays for detecting carbapenemase-producing Enterobacterales (CPE). Methods: 151 Enterobacterales isolates were collected, the sensitivity and specificity of each test was determined, with molecular genotype serving as the gold standard. The phenotypic evaluations were performed using EDTA-synergistic carbapenem inactivation method (esCIM), EDTA-carbapenem inactivation method (eCIM), and enzyme inhibitor enhancement experiment (EIE). Results: The concordance rate was 98% for the EIE for the detection of KPC producer, and 100% for the esCIM and eCIM. Sensitivity differed among the 3 methods, and all assays had excellent sensitivity exceeding 90% for detecting metallo-β-lactamases (MBLs). The specificity of the eCIM, esCIM and EIE was 100%, 100% and 95%. Both eCIM and esCIM were unsatisfactory in detecting multi-enzyme strains (MBL and class A serine carbapenemase) (0/6). However, EIE increased the positive number to six (6/6). Conclusions: The eCIM, esCIM and EIE can be used to accurately detect and distinguish carbapenemase and is suitable for routine use in most clinical microbiology laboratories.